2022
DOI: 10.3390/biomedicines10020490
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Genome in Aging and Disease and the Future of Mitochondrial Therapeutics

Abstract: Mitochondria are intracellular organelles that utilize nutrients to generate energy in the form of ATP by oxidative phosphorylation. Mitochondrial DNA (mtDNA) in humans is a 16,569 base pair double-stranded circular DNA that encodes for 13 vital proteins of the electron transport chain. Our understanding of the mitochondrial genome’s transcription, translation, and maintenance is still emerging, and human pathologies caused by mtDNA dysfunction are widely observed. Additionally, a correlation between declining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 174 publications
(189 reference statements)
0
5
0
Order By: Relevance
“…The telomere length, a marker of biological aging [ 73 ], was also not significantly affected in response to prenatal BPA exposure. Similarly, mitochondrial DNA copy number (mtDNA-CN), associated with several aging-related diseases [ 74 , 75 ] and lipofuscin accumulation, was not affected by prenatal BPA exposure and is represented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The telomere length, a marker of biological aging [ 73 ], was also not significantly affected in response to prenatal BPA exposure. Similarly, mitochondrial DNA copy number (mtDNA-CN), associated with several aging-related diseases [ 74 , 75 ] and lipofuscin accumulation, was not affected by prenatal BPA exposure and is represented in Figure 4 .…”
Section: Resultsmentioning
confidence: 99%
“…associated with several aging-related diseases [74,75] and lipofuscin accumulation, was not affected by prenatal BPA exposure and is represented in Figure 4. associated with several aging-related diseases [74,75] and lipofuscin accumulation, was not affected by prenatal BPA exposure and is represented in Figure 4.…”
Section: Effect Of Prenatal Bpa Exposure On Markers Of Longevity and ...mentioning
confidence: 99%
“…A recent hypothesis also suggested that the mitochondria may under the influence of microbial pathogens can transform themselves into super-power cells or immortal cancer cells that enable tumor formation [ 55 ]. In view of the potential role of mtDNA in aging and diseases including cancers, the role of gene editing in therapeutic management was being explored [ 56 ].…”
Section: Reviewmentioning
confidence: 99%
“…Серія «Тваринництво», випуск 2 (49), 2022 of the electron transport chain, 22 tRNAs and 2 rRNAs (Hieu Duc Nguyen, 2017; Anjana Saravanan, 2022). The mitochondrial genome has one major non-coding region -the D-loop, which is where the transcription and replication factors encoded by the kernel interact, which travel to the mitochondria to initiate transcription, and then replication of the mitochondrial genome.…”
Section: вісник сумського національного аграрного університетуmentioning
confidence: 99%